Correlated evolution of morphology, gas exchange, growth rates and hydraulics as a response to precipitation and temperature regimes in oaks (Quercus). Issue 3 (20th December 2019) - Ramírez‐Valiente, José Alberto; López, Rosana; Hipp, Andrew L.; Aranda, Ismael
Summary: It is hypothesised that tree distributions in Europe are largely limited by their ability to cope with the summer drought imposed by the Mediterranean climate in the southern areas and by their competitive potential in central regions with more mesic conditions. We investigated the extent to which leaf and plant morphology, gas exchange, leaf and stem hydraulics and growth rates have evolved in a coordinated way in oaks ( Quercus ) as a result of adaptation to contrasting environmental conditions in this region. We implemented an experiment in which seedlings of 12 European/North African oaks were grown under two watering treatments, a well‐watered treatment and a drought treatment in which plants were subjected to three cycles of drought. Consistent with our hypothesis, species from drier summers had traits conferring more tolerance to drought such as small sclerophyllous leaves and lower percent loss of hydraulic conductivity. However, these species did not have lower growth rates as expected by a trade‐off with drought tolerance. Overall, our results revealed that climate is an important driver of functional strategies in oaks and that traits have evolved along two coordinated functional axes to adapt to different precipitation and temperature regimes. Abstract : See also the Commentary on this article by Cavender‐Bares et al., (2020) 227 : 659–663 .